Preparation, Antidermatophyte Activity, and Mechanism of Methylphloroglucinol Derivatives - Ye, Lianbao; Lin, Pengfei; Du, Wenjun; Wang, Yuanyuan; Tang, Chunping; Shen, Zhibin (Frontiers in Microbiology, 2018)
In this study a variety of phloroglucinols were isolated from the plant, and the activity experiment showed that the phloroglucinols had strong antifungal activity, especially methylphloroglucinol derivatives such as aspidin PB, dryofragin, aspidinol, aspidin BB, aspidin AB, and albicanol, in which the hydroxyl group of methylphloroglucinol is the active group of compounds, and C-2 or C-6 is the active site. The introduction of different groups in this position could change the properties and bioactivity of the compounds. In this study, different functional groups were introduced to the structure of methylphloroglucinol to obtain methylphloroglucinol derivatives that were synthesized, and antidermatophyte activities on Trichophyton rubrum, Trichophyton mentagrophytes, Microsporum canis, and Gypsum microspore bacteria were evaluated. Molecular docking verified its ability to combine the protein binding site. The antidermatophyte mechanism of compounds on cytochrome P450 sterol 14a-demethylase, squalene epoxidase, and β-1,3-glucan synthase was investigated by the enzyme-linked immunosorbent assay. The results showed that compounds had an inhibitory effect on four kinds of common dermatophytes in varying degrees, in which compound g had the strongest activities, the binding mode of methylphloroglucinol and its derivatives were similar to those of three enzymes, and compounds e and g had significant effects on the activity of the three enzymes, and compound g had a slightly stronger effect than the blank group. Compounds e and g also had a significant effect on the ergosterol synthesis of M. canis. This study could supply some antidermatophyte leading structure and possible mechanism for studying and developing new antifungal agents.